Architecture in the Monks - Rouge | Charles.... (National Library of France)
Notice issue d Europeana. Part of the documentary ensemble: BNUStr003
Droits : http://rightsstatements.org/vocab/NoC-OKLR/1.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie; Iconographie